Human diet and nutrition in biocultural perspective : past meets present - Moffat, Tina, 1967-; Prowse, Tracy Lynn (New York : Berghahn Books, 2010)
There are not many areas that are more rooted in both the biological and social-cultural aspects of humanking than diet and nutrition. Throughout human history nutrition has been shaped by political, economic, and cultural forces, and in turn, access to food and nutrition has altered the course and direction of human societies. Using a biocultural approach, the contributors to this volume investigate the ways in which food is both an essential resource fundamental to human health and an expression of human culture and society. The chapters deal with aspects of diet and human nutrition through space and time and span prehistoric, historic, and contemporary societies spread over various geographical regions, including Europe, North America, Africa, and Asia to highlight how biology and culture are inextricably linked. --Book Jacket.
Introduction : a biocultural approach to human diet and nutrition / T. Moffat, T. Prowse -- 1. What did humans evolve to eat? Metabolic implications of major trends in hominid evolution / W.R. Leonard, M.L. Robertson, J.J. Snodgrass -- 2. Child growth among southern African foragers in the past / S. Pfeiffer, L. Harrington -- 3. Infant and young child feeding in human evolution / D.W. Sellen -- 4. The use of stable isotope analysis to determine infant and young child feeding patterns / T.L. Dupras -- 5. A community in transition : deconstructing breastfeeding trends in Gibralter, 1955-1996 / L.A. Sawchuk, E.K. Bryce, S.D.A. Burke -- 6. Dietary diversity, dietary transitions, and childhood nutrition in Nepal : questions of methodology and practice / T. Moffat, E. Finnis -- 7. Responses to a food crisis and child malnutrition in the Nigerien Sahel / R.E. Casiday, K.R. Hampshire, C. Panter-Brick, K. Kilpatrick -- 8. Growth, morbidity, and mortality in antiquity : a case study from Imperial Rome / T. Prowse, S. Saunders, C. Fitzgerald, L. Bondioli, R. Macchiarelli -- 9. Examining nutritional aspects of bone loss and fragility across the life course in bioarchaeology / S.C. Agarwal, B. Glencross -- 10. Obesity : an emerging epidemic : temporal trends in North America / P.T. Katzmarzyk -- Conclusion : diet and nutrition in biocultural perspective : back to the future / T. Prowse, T. Moffat.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Food habits; Diet; Nutrition; Diet in disease; Nutritional Physiological Phenomena; Diet; Feeding Behavior; Sociobiology; Habitudes alimentaires; Alimentation; Nutrition; Régimes alimentaires; diet; SOCIAL SCIENCE -- Customs & Traditions; SOCIAL SCIENCE -- Anthropology -- Cultural; Diet in disease; Diet; Food habits; Nutrition